Dazzle ships : World War I and the art of confusion - Barton, Chris (Millbrook Press, 2017)
"When the British Royal Navy grew desperate to protect their ship from German U-Boat attacks, they created Dazzle ships in order to confuse the enemy of their location and destination."--Provided by publisher.